Grounded (Re-)Construction of the Self-Reflection Core Competence from Statements of Adult Education Professionals - Anita Pachner (Adult Education Research Conference, 2014)
This article discusses the significance that is assigned to the core competence of self-reflection by adult education professionals. Therefore, a conceptual classification in connection with the research design and initial results of an empirical study will be introduced with the intention of providing a grounded (re-)construction of the self-reflection competence.